POKOK-POKOK PIKIRAN UPAYA PEMBERDAYAAN MASYARAKAT PERTANIAN MELALUI PELAYANAN MINIMAL PENYULUHAN PERTANIAN DI BPP - Zahron Helmy (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2005)
Success in agricultural development is result the developed and self-reliant nation in agricultural there is dynamic reciprocal relationship between agricultural sector development and human development